Evaluasi Penerapan Sistem Pengendalian Internal Atas Persediaan Bahan Baku Pada ABC Company - Fauzi Alfarisi; Rina Nurmalina; Hastuti Hastuti; Putry Handayani Nadeak (Jurusan Akuntansi Politeknik Negeri Bandung, 2026)
This study evaluates the implementation of the Internal Control System (ICS) over raw material inventory at ABC Company. A descriptive qualitative approach was employed through interviews, observations, and documentation. Interview data were analyzed using NVivo 12 Pro to develop a Control Matrix for evaluating internal controls based on the 2013 Committee of Sponsoring Organizations of the Treadway Commission (COSO) Internal Control–Integrated Framework. The findings indicate that the company has implemented internal controls through segregation of duties, periodic stock opname, purchasing verification, goods receipt inspection, the Point of Sales (POS) system, and operational monitoring. However, weaknesses remain in formal risk assessment documentation, inventory system integration, and internal control evaluation. This study recommends strengthening risk documentation, improving system integration, and enhancing internal control evaluation based on the COSO framework.